Solar Panel Technology for the Treatment of Eucalyptus Oil Refined Waste - Rahmat, Saepul; Purnata, Hendi; Ilahi, Novita Asma; Musyafiq, Afrizal Abdi; Dewi, Riyani Prima (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Banjarwaru Village, Nusawungu District, Cilacap Regency, has natural resources, especially eucalyptus plants, which have the potential to develop the economy of the village community. The biggest problem faced by LMDH Dadi Makmur as a unit that manages the eucalyptus oil business is that after the production of eucalyptus oil distillation, it will produce residual waste from eucalyptus twigs and leaves with quite a large volume and only allowed to be piled up around the yard where the distillery is, causing area storage of essential oil raw materials is narrow and also takes a long time to become organic fertilizer. The innovation offered through this community service activity is implementing a briquette printing machine from eucalyptus oil refining waste, which is energy efficient and based on solar panels. The dedication results show that the eucalyptus oil waste processing activity and reducing environmental pollution also produce biomass briquettes that the residents of Banjarwaru Village can utilize as a leading economic product of Banjarwaru Village. The test data of the briquette making machine shows that the output voltage from the inverter produces an AC voltage with a value of 216 - 221 V, so that it can rotate the AC motor with a rotation of 800 - 1400 rpm.